Concrete consoles impact to a masonry walls building with a large hall at the top story and a lightweight timber roof. Issue 1 (1st April 2022) - Constantinescu, S
Abstract: The paper studies the behavior of a medium height masonry walls building, placed in Satu Mare (Romania). It contains large balcony consoles and a large hall at the top story, covered by a timber roof. The roof trusses sit at both ends on the external walls. The study's purpose is to determine the importance of large slab consoles and walls buttresses at the top story, for the structure. The paper compares the structure's behavior in 3 cases. The first contains both large consoles and wall spurs, the second only incorporates pier buttresses and the third holds just the balcony consoles. The structure's behavior for both the elastic and plastic stage is compared for the 3 cases. The plastic stage shows the bending moment's distribution in slabs and stresses in masonry walls during stages when they surpass the masonry strengths. The plastic hinges development at structure collapse and the pushover diagrams for each case along with the results interpretation are presented. A nonlinear analysis is done for the timber roof also, for both orthogonal directions. The study shows both large consoles and halls at the top floor are appropriate for masonry structures, if designed correctly.